Keterbatasan Pengadilan untuk Melakukan Pengujian Konstitusional (Constitutional Review): Pengalaman Jepang - Isharyanto (Law Faculty of Universitas Bandar Lampung, 2015)
The realm of political practice today , a mechanism for checking the legalnorms by the court to ensure the coherence of the legislation of the constitution becomes inevitable (judicial constitutional review ) . Learning the Japanese experience , that constitutionalism is the reconstruction of post-war Japan ystem ystem kenegaran of civil law -based rule by law be a constitutionalism which is based on the rule of law . Keywords : court , the Constitutional Review , Japan